Angiotensin-converting enzyme inhibitor or angiotensin receptor blocker use is associated with reduced major adverse cardiovascular events among patients with critical limb ischemia - Armstrong, Ehrin J; Chen, Debbie C; Singh, Gagan D; Amsterdam, Ezra A; Laird, John R (Vascular medicine (London, England), 2015)
Angiotensin converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) are recommended for secondary prevention in peripheral artery disease, but their effectiveness in patients with critical limb ischemia (CLI) is uncertain. We reviewed 464 patients with CLI who underwent diagnostic angiography or endovascular intervention from 2006–2013 at a multidisciplinary vascular center. ACEI or ARB use was assessed at the time of angiography. Major adverse cardiovascular events (MACE), mortality, and major adverse limb events (MALE) were assessed during three-year follow-up. Propensity weighting was used to adjust for baseline differences between patients taking and not taking ACEIs or ARBs. ACEIs or ARBs were prescribed to 269 (58%) patients. Patients prescribed ACEIs or ARBs had more baseline comorbidities including diabetes and hypertension (p<0.05). Patients prescribed ACEIs or ARBs had lower three-year unadjusted rates of MACE (40% versus 47%) and mortality (33% versus 43%). After propensity weighting, ACEI or ARB use was associated with significantly lower rates of MACE (hazard ratio [HR] 0.76, 95% confidence interval [CI] 0.58–0.99, p=0.04) and overall mortality (HR 0.71, 95% CI 0.53–0.95, p=0.02). There was no significant association between ACEI or ARB use and MALE (HR 0.97, 95% CI 0.69–1.35, p=0.2) or major amputation (HR 0.74, 95% CI 0.47–1.18, p=0.1). ACEI/ARB use is associated with lower MACE and mortality in patients with CLI, but there was no effect on limb-related outcomes.